Performance Evaluation of Fractal Array Antenna for Small Satellite Applications - Yemane Ghebremedhin Teklehaimanot; Sinshaw Bekelle; Mohammed Ismail (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The possible antenna which can be integrated with relatively large flat structure of solar panel of small satellites is patch antenna. The main problem of common Microstrip patch antennas is that they only operate at one or two frequencies, restricting the number of bands that equipment is capable of supporting. Another issue is that, due to the very strict space that a solar panel has, setting up more antenna array is very difficult. To reduce these problems, the use of fractal shaped antennas integrated on solar cells will be analyzed. The small satellite applications demand a high efficient multi-band antenna with a very compact size. A 2x2 Sierpinski Fractal antenna array is modeled and simulated using HFSS. The proposed work has resulted in multiband operation 10.2 GHz and 18.3GHz with increased bandwidth and radiation characteristics betterment, with added advantage of light weight and smaller dimension which is important where cost to payload is a constraint in satellites.